Kultura gospodarcza cywilizacji zachodniej – jej istota, sprzeczności i znaczenie dla rozwoju w skali globalnej - Michalski, Michał A. (Człowiek i Społeczeństwo, 2014)
The article presents an analysis of economic culture of the Western civilization in the context of its current shape and condition. Although this topic has already been chosen as the subject of research in the past, in this paper the stress is put on those aspects that do not seem to be very popular. To look at the uniqueness of the Western civilization in the context of a globalized world may seem incorrect to some extent, but in our opinion it is still necessary if we want to explore and to discover the sources of unprecedented growth and development that not only the West have benefited from. The article thereby contributes to the field of the research of the impact of culture on the socioeconomic order. The paper therefore seeks to offer an explanation of the specific path that the Western civilization has followed, because it is important in the context of the future dilemmas of global society, which needs to find solutions to its different challenges and problems. Besides discussing the contribution of such recognized authors as Max Weber and Peter L. Berger, the article analyses the role of mediating structures (with special reference to the family) and cultural contradictions which seriously influence the shape and condition of the West these days.